(untitled) (Revista Contexto & Saúde, 2026)
Recent evidence has shown the presence of high prevalence of depression, anxiety, stress, trauma, and insomnia problems among hospital healthcare workers (HCWs) during the Covid-19 pandemic. We aim to identify psychosocial and sociodemographic predictors of depression among HCWs at hospitals during the pandemic. A cross-sectional online survey was carried out between July 2020, and January 2021, with 384 HCWs from southern Brazil. Depression rates were assessed by the Center for Epidemiologic Studies Depression Scale (CES-D), and psychosocial aspects (vulnerability to stress at work, perception of stigma, sociodemographic, health, and labor variables) were assessed. Associations were tested using multiple linear regression (Stepwise method). About 79% of HCWs showed depression at a clinical level, and scores were higher among women, people without a partner, and among those who perceived a worse organizational climate and functioning, higher pressure at work, stigma, and social devaluation related to HCWs. The work climate measure explained 24.3% of depression levels. We discuss actions to manage mental health risks related to the healthcare labor context and the long-term psychosocial consequences of pandemic outbreaks.